The effects of a researcher’s presence during VR experiments - Siljehav Ozimek,Sebastian; Nilsson,Niclas (LUTVDG/TVBB, 2026)
The aim of this study is to investigate if a researchers presence affects participants performing a virtual reality evacuation, and if by removing the researcher, the results better resemble the results produced in a real world experiment. Initially, a study on previous research in human behaviour in fire, the effect of a researcher's presence and Virtual reality experiments was conducted. 54 participants, divided into two groups, performed experiments in VR. One group had a researcher present in the room, and the other group of participants were left alone during the experiment. While the participants performed the experiment, a virtual fire alarm would sound and their reactions to the alarm were documented. At the end of the experiment, all participants answered three questions verbally while still being in VR. The results from the different groups were then compared. The results from this experiment showed that by removing the researcher from the room, the number of participants reacting to the fire alarm when in a virtual environment increased. Thus producing results that closer resemble the results from the real world experiment done by Arias et al. (2025). This suggests that the physical presence of a researcher may influence participant behavior in VR experiments.
Keywords: Virtual Reality; experiments in Virtual Reality; researchers influence during experiments; human behaviour; impact on participants; fire alarm